Penggunaan Instrumen Cello Dalam Langgam Jawa - Sudarno Sudarno (Institut Seni Indonesia Yogyakarta, 2017)
Keroncong music is the result of a mixture of Portuguese culture and Indonesian culture around the year 1498. Java Javanese style which is one part of keroncong music develops well in Java as a form of community creativity. In 1934 was used pitchicato cello instrument that is picked the technique of strumming with fingers, by Tjok Shinsu. The cello instrument in its native country is a string instrument, by the Indonesians being transformed into a string instrument now known as